Associations between skeletal muscle strength and chronic kidney disease in patients with MASLD - Zhang, Xin-Lei; Gu, Yeqing; Zhao, Jing; Zhu, Pei-Wu; Chen, Wen-Ying; Li, Gang; Liu, Wen-Yue; Zheng, Wen; Zhang, Ni; Chen, Li-Li; Targher, Giovanni; Byrne, Christopher D.; et al. (Communications medicine, 2025)
Background A skeletal muscle strength (SMS) decline is associated with metabolic diseases, but whether SMS also declines with chronic kidney disease (CKD) in individuals with metabolic dysfunction-associated steatotic liver disease (MASLD) is uncertain. This study examined the associations between SMS and the risk of CKD in MASLD population. Method We performed a large-scale study with four cohorts: PERSONS and NHANES 2011–2014 cohorts for the cross-sectional investigation, and TCLSIH and UK Biobank cohorts for the longitudinal investigation. A handgrip dynamometer measured handgrip strength as a proxy for overall SMS. Participants were stratified according to CKD status [non-CKD vs. CKD (stages 1–5) groups]. Results In the PERSONS cohort, the CKD group has a lower handgrip strength than the non-CKD group (27.14 ± 9.19 vs. 33.59 ± 11.92 kg, P < 0.001). Higher handgrip strength is associated with lower odds of abnormal albuminuria or CKD (OR: 0.96, 95%CI:0.92-0.99 and OR:0.95, 95%CI: 0.91-0.99 respectively). The highest handgrip strength tertile is associated with the lowest risk of having abnormal albuminuria or CKD (compared with the lowest or middle tertile). Results are similar in NHANES cohort. Furthermore, the highest handgrip strength is independently associated with the lowest risk of incident CKD in MASLD (HR: 0.95, 95%CI: 0.92-0.99 and HR:0.99, 95%CI: 0.98-0.99 in TCLSIH and UK Biobank cohorts). In Kaplan-Meier curve analysis, the cumulative incidence of CKD is lowest in the highest handgrip strength tertile compared to the lowest or the middle tertile. Conclusions Higher handgrip/muscle strength is independently associated with a lower risk of CKD and abnormal albuminuria in MASLD population. Plain language summary Metabolic dysfunction-associated steatotic liver disease (MASLD) occurs when there is too much fat in the liver. People with MASLD have an increased risk of developing chronic kidney disease (CKD). Skeletal muscles are responsible for voluntary movements and are crucial for movement and health. We investigated whether skeletal muscle strength (SMS), assessed using handgrip strength, was associated with the risk of CKD in individuals with MASLD. Based on data from over 14,000 participants we found that higher SMS was associated with a lower risk of CKD. These findings suggest that preserving skeletal muscle strength may help prevent people with MASLD developing kidney disease. Zhang and Gu used four cohorts to examine associations between skeletal muscle strength (SMS) and chronic kidney disease (CKD) in people with metabolic dysfunction-associated steatotic liver disease (MASLD). Higher handgrip/muscle strength is closely associated with a lower prevalence and incidence of CKD in people with MASLD.